Visualization of Intrapulmonary Lymph Vessels in Healthy and Inflamed Murine Lung Using CD90/Thy-1 as a Marker - Kretschmer, Sarah; Dethlefsen, Ina; Hagner-Benes, Stefanie; Marsh, Leigh M.; Garn, Holger; König, Peter (PLOS ONE, 2013)
Background Lymphatic vessels play a pivotal role in fluid drainage and egress of immune cells from the lung. However, examining murine lung lymphatics is hampered by the expression of classical lymph endothelial markers on other cell types, which hinders the unambiguous identification of lymphatics. The expression of CD90/Thy-1 on lymph endothelium was recently described and we therefore examined its suitability to identify murine pulmonary lymph vessels under healthy and inflammatory conditions. Methodology/Principal Findings Immunohistochemistry with a monoclonal antibody against CD90.2/Thy-1.2 on 200 µm thick precision cut lung slices labeled a vascular network that was distinct from blood vessels. Preembedding immunostaining and electron microscopy verified that the anti-CD90.2/Thy-1.2 antibody labeled lymphatic endothelium. Absence of staining in CD90.1/Thy-1.1 expressing FVB mice indicated that CD90/Thy-1 was expressed on lymph endothelium and labeling was not due to antibody cross reactivity. Double-labeling immunohistochemistry for CD90/Thy-1 and α-smooth muscle actin identified two routes for lymph vessel exit from the murine lung. One started in the parenchyma or around veins and left via venous blood vessels. The other began in the space around airways or in the space between airways and pulmonary arteries and left via the main bronchi. As expected from the pulmonary distribution of lymph vessels, intranasal application of house dust mite led to accumulation of T cells around veins and in the connective tissue between airways and pulmonary arteries. Surprisingly, increased numbers of T cells were also detected around intraacinar arteries that lack lymph vessels. This arterial T cell sheath extended to the pulmonary arteries where lymph vessels were located. Conclusions/Significance These results indicate that CD90/Thy-1 is expressed on lymphatic endothelial cells and represents a suitable marker for murine lung lymph vessels. Combining CD90/Thy-1 labeling with precision cut lung slices allows visualizing the anatomy of the lymphatic system in normal and inflamed conditions.